2018
DOI: 10.1111/odi.12895
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of parathyroid hormone and strontium ranelate on bone healing in ovariectomized rats

Abstract: Parathyroid hormone and SR combinations can be effective for calvarial bone regeneration of ovariectomized rats. PTH plus SR may have potential use as bone graft material in orthopedic and dental surgery to enhance bone healing and osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…Chitosan microparticles encapsulating PTH were compressed into tablet implants consisting of strontium and poloxamer. PTH+SR implants showed statistically greater new bone formation in calvarial defects than either treatment alone at both 4 weeks and 8 weeks [303]. The study also reported similar quantities of new bone formation using PTH implants alone and Sr implants alone.…”
Section: Strontiumsupporting
confidence: 60%
“…Chitosan microparticles encapsulating PTH were compressed into tablet implants consisting of strontium and poloxamer. PTH+SR implants showed statistically greater new bone formation in calvarial defects than either treatment alone at both 4 weeks and 8 weeks [303]. The study also reported similar quantities of new bone formation using PTH implants alone and Sr implants alone.…”
Section: Strontiumsupporting
confidence: 60%
“…It is biocompatibile, antibacterial and its production is easy. Various studies have tested chitosan as a factor and/or drug delivery system for pharmaceutical and tissue engineering applications [5,17].…”
Section: • Gelatinmentioning
confidence: 99%
“…Owing to the drawbacks and limitations of bone grafts, over the last few decades, several novel approaches involving tissue engineering and regenerative medicine (TE/RM) have emerged as alternatives to conventional treatments. The fundamental concept underlying TE/RM was to use scaffolds alone or in combination with growth factor, cell and/or gene delivery to form a so-called "tissue engineering construct," that stimulates tissue repair and/or regeneration [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Göker et al. (2018) showed that combining PTH with strontium ranelate significantly increased new bone formation and improved osseointegration in ovariectomized rats. Osteoblasts transfected with miR‐185 mimics or siRNA against PTH could decrease the levels of PTH, Wnt, and β‐catenin.…”
Section: Figurementioning
confidence: 99%